Significance of Pseudomeningocele After Decompressive Surgery for Chiari I Malformation - Balasa, Artur; Kunert, Przemysław; Bielecki, Mateusz; Kujawski, Sławomir; Marchel, Andrzej (Frontiers in Surgery, 2022)
Background: Pseudomenigoceles (PMCs) as abnormal collections of cerebrospinal fluid are quite common findings on follow-up MRI after Chiari decompression surgery (CDS). However, the importance of their identification has not been truly determined, especially when PMCs are described occasionally in the process of radiological follow-up. We retrospectively analyzed surgical outcomes and imaging findings after CDS depending upon the occurrence and thickness of PMCs. Methods: A total of 76 adult patients who underwent CDS were analyzed. The clinical and radiological outcomes of patients with a pseudomenigocele (wPMC) were evaluated and compared to those of patients without a pseudomenigocele (w/oPMC). Radiological morphometric measurements were performed and compared between groups. Comparisons of the maximal PMC thickness were made within the wPMC group. Results: PMCs were recognized in 27 (35.5%) patients, of whom 3 (11.1%) required reoperation. Differences in satisfactory result rates regarding gestalt assessment and Chicago Chiari Outcome Scales were statistically insignificant between the w/oPMC and wPMC groups (p=1 and p=0.56, respectively). The postoperative syringomyelia decrease and cerebellar tonsil elevation were similar between the groups (p=1 and p=0.74, respectively) in the long-term follow-up. Additionally, the clinical or radiological outcomes with radiological details were not related to PMC thickness in the long-term follow-up. However, radiological details showed the cooccurrence of PMCs with a postsurgical of cerebello-tentorial distance increase (p<0.05), basion-pontomedullary sulcus distance decrease (p<0.05) and tonsillo-graft distance decrease (p<0.05). Conclusions: We found no significant relationships between PMC presence or thickness and clinical or radiological outcomes. However, postoperative changes within the posterior fossa associated with PMCs resemble brain sagging, which occurs in intracranial hypotension. Therefore, extradural cerebrospinal fluid escape may also be responsible for symptoms in some patients with PMCs after CDS.